Grief among Neonatal Intensive Care Nurses. Issue 4 (July 2020) - Rodriguez, Alison; Spilker, Arlene; Goyal, Deepika
Abstract: Background: Nurses working in the high-stress environment of the neonatal intensive care unit (NICU) are at high risk of experiencing grief after death of a baby. Design: Using a quantitative cross-sectional design, a convenience sample of nurses working in a Level IV NICU in Northern California, United States completed online surveys. Level of grief among NICU nurses, perceptions of grief support available at their institution, and past and future grief coping methods were assessed. Participants: A diverse sample of 55 NICU nurses, mean age 45.5 (SD = 11.7) years. Setting: A high-acuity NICU in one large Northern California hospital. Methods: Participant demographic data and the Revised Grief Experience Inventory were completed online. Results: Total grief scores ranged between 22 and 82 with a mean of 46.9 (SD = 17.4). Sixty percent (n = 33) moderately/strongly disagreed on adequacy of current grief support services at their institution and 81% (n = 45) reported hospital staff could benefit from additional grief support. Nurses' past grief support included family, friends, and church. Future grief resources would include family, friends, and co-workers. Participants indicated need for debriefing and additional nurse staffing resources at the time of a patient death. Conclusions: Neonatal intensive care unit nurses in our study reported experiencing grief. Debriefing and bereavement support may be helpful for nurses working in high-stress environments where there is a higher likelihood of patient death. Abstract : Nurses in the neonatal intensive care unit (NICU) experience grief when an infant death occurs. In this study, the grief experience of NICU nurses is explored and recommendations for supporting them are offered.